Determinacy of interest rate rules with bond transaction services in a cashless economy - Massimiliano Marzo; Paolo Zagaglia (Bank of Finland, 2008)
Canzoneri and Diba (2004) show that the Taylor principle is not a panacea for equilibrium determinacy in a model where bonds and money provide liquidity services to households. We consider a cashless New Keynesian model with two types of government bonds. One bond provides transaction services, whereas the other is used only as a store of value. We show that the Taylor principle is still sacrosanct, and that the results of Leeper (1991) are confirmed.
URN:NBN:fi:bof-20140807222
Keywords: E52; C68; 330; monetary policy; fiscal policy; government bonds; determinacy